Biogeochemical data of sinking particulate matter collected by sediment trap mooring 07-01 (2017-2018) in the South Indian Ocean - Natalie Harms; Niko Lahajnar; Ulrich Schwarz-Schampera (PANGAEA, 2021)
The Universität Hamburg is part of the environmental studies in the INDEX (Indian Ocean Exploration) program, which was established by the BGR (Federal Institute for Geosciences and Natural Resources), Hanover. The INDEX license area is located in the oligotrophic subtropical gyre of the South Indian Ocean. Sinking particulate matter samples were collected by sediment trap mooring 07-01 to measure vertical particle flux quantitatively and qualitatively. Mooring 07-01 was deployed during cruise SO259 (RV Sonne) and recovered during cruise PE446 (RV Pelagia).